Impacto nutricional de pacientes em quimioterapia - COSTA, Gleidison Andrade (2023)
Introduction: Changes in the nutritional status of cancer patients undergoing chemotherapy have adverse impacts on all phases of treatment. Objective: To assess the nutritional status of patients undergoing chemotherapy. Methods: A cross-sectional study with 150 patients, data collected through two questionnaires. Data were analyzed using the Statistical Package for the Social Sciences, version 20.0, applying the Komogorov-Smirnov test to check if the data followed a normal distribution, examining the difference in anthropometric variables with nutritional impact symptoms through the Student's t-test and the non-parametric U Mann- Whitney. The adopted significance level was p<0.05. Results: Two scientific articles were produced, one in the Integrative Review format and the other in the Field Research format. Through the latter, it was observed that of the 150 evaluated patients, 62.0% were female, 56.7% were adults, and 66.7% were from the interior of the state. In the classifications of nutritional parameters, 48.0% of patients were eutrophic by body mass index, indicating some degree of malnutrition by arm circumference (56.7%) and tricipital skinfold (62.7%). In the evaluation of muscle mass by arm muscle circumference, 57.3% were eutrophic, but by calf circumference, 55.3% were below the appropriate cutoff points. According to the Subjective Global Assessment Produced by the Patient, 21.3% were classified as "well-nourished," 58.7% as "moderately malnourished," and 20% as "severely malnourished." The most recurrent symptom was "nausea," at 53.3%; other symptoms were in a smaller proportion but reflected in the variable "difficulty in eating" (87.3%). Statistically significant associations were observed between the presence of mucositis and body mass index (p-0.029), mucositis and calf circumference (p-0.029), and xerostomia and tricipital skinfold (p-0.003). In the overall physical examination, 68.7% showed some degree of nutritional deficit. Conclusion: It is emphasized that the use of different tools in nutritional care for cancer patients undergoing chemotherapy is important for the adequate diagnosis, symptom management, and dietary intervention.